Metallothioneins in biochemistry and pathology - Zatta, Paolo (World Scientific Pub. Co., 2008)
This important book explores the role of MTs in the field of neurological disorders (brain inflammation, Alzheimer's and prion diseases, autism, ALS, etc.), cardiology (cardiomyopathy, atherosclerosis), and oncology (melanoma, prostate and breast cancer), through authoritative contributions and a description of basic biochemical information and paradigmatic pathological events.